Políticas públicas agroalimentares: o direito à informação dos consumidores brasileiros a luz dos modelos latino-americanos e europeu. - Quadrado, Hebert Fabricio Tortorelli [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
A fome é um problema mundial e o Brasil não está fora dessa realidade. A busca pela segurança alimentar precisa levar em consideração os aspectos produtivos, de consumo, de sustentabilidade e de saúde pública, dentre outros. Como o direito à alimentação é um direito social, o Estado precisa agir para que o mesmo seja assegurado. Assim, a atuação estatal via políticas públicas agroalimentares - instrumentos voltados à garantia da segurança alimentar e nutricional que afetam a dignidade da pessoa humana – deve ocorrer de forma a buscar assegurar a sustentabilidade, já que a presente e as futuras gerações devem ter suas condições de vida preservadas. De forma mais imediata, também é necessário que o Estado garanta o direito à informação no âmbito alimentar, de forma que os consumidores possam ter clareza sobre aquilo que estão ingerindo, para facilitar escolhas saudáveis e sustentáveis. No cenário da globalização e pela relevância do tema para a sociedade, a questão pode ser tratada até mesmo no âmbito de blocos econômicos, já que podem ter implicações comerciais e cidadãs. A pesquisa busca tratar do problema relacionado a uma contradição entre um mundo que busca, ao menos desde os anos 2000, atingir metas de sustentabilidade alimentar, mas que ao menos no Ocidente aumenta cada vez mais a base de sua dieta em produtos alimentícios advindos da agroindústria, o que demanda estudos para verificar se o setor produtivo tem se preocupado com a qualidade do que oferece ao consumidor alimentar e como interfere no meio natural. O presente trabalho tem como objetivos explicitar o cenário de interseção entre segurança alimentar, sustentabilidade e os dezessete Objetivos de Desenvolvimento Sustentável (ODS) da Organização das Nações Unidas (ONU); a análise de políticas públicas agroalimentares direcionadas ao direito à informação dos consumidores, considerando os marcos da sustentabilidade impostos pelo ODS 12 (consumo e produção responsáveis) e como elas podem influenciar na segurança alimentar brasileira.

Hunger is a global problem and Brazil is not outside this reality. The search for food security needs to take into account production, consumption, sustainability and public health aspects, among others. As the right to food is a social right, the State needs to act to ensure it. Thus, state action via agri-food public policies - instruments aimed at guaranteeing food and nutritional security that affect the dignity of the human person - must occur in a way that seeks to ensure sustainability, since the present and future generations must have their own conditions of lives preserved. More immediately, it is also necessary for the State to guarantee the right to information in the food sector, so that consumers can be clear about what they are eating, to facilitate healthy and sustainable choices. In the scenario of globalization and due to the relevance of the topic for society, the issue can be addressed even within the scope of economic blocs, as it can have commercial and civic implications. The research seeks to address the problem related to a contradiction between a world that has sought, at least since the 2000s, to achieve food sustainability goals, but which, at least in the West, increasingly relies on food products from the agro-industry, which demands studies to verify whether the production sector has been concerned with the quality of what it offers to the food consumer and how it interferes with the natural environment. The present work aims to explain the intersection scenario between food security, sustainability and the seventeen Sustainable Development Goals (SDGs) of the United Nations (UN); the analysis of agri-food public policies aimed at consumers' right to information, considering the sustainability milestones imposed by SDG 12 (responsible consumption and production) and how they can influence Brazilian food security. Using the hypothetical-deductive methodology, making use of comparative law, through bibliographic-descriptive research, the objective was to examine the models adopted in Latin America and Europe and compare them with the Brazilian model, finally verifying , that the Brazilian model is close to that of the European Union and contributes to promoting responsible consumption and respect for consumers' right to information, in addition to helping to create a culture of food safety in the country.
Agri-food public policies: the right to information of Brazilian consumers in the light of Latin American and European models.
Keywords: Direito agrário; Políticas públicas agroalimentares; Direito à informação dos consumidores; Agrarian law; Agri-food public policies; Consumers' right to information